The Basel capital requirement, lending interest rate, and aggregate economic growth: An empirical study of Viet Nam - Nguyet Thi Minh Phi; Hanh Thi Hong Hoang; Farhad Taghizadeh-Hesary; Naoyuki Yoshino (Asian Development Bank Institute (ADBI), 2019)
In recent years, the Vietnamese economy has shown signs of financial distress, and especially small banks have experienced serious liquidity and solvency problems. Based on the new policy of the State Bank of Vietnam, in order to ensure safe and effective banking operations, the Basel II accord will be widely applied to the whole banking system by 2018. This paper investigates the effects of the Basel II capital requirement implementation in Viet Nam on the bank lending rate and national output. The paper provides a theoretical framework as well as empirical model by developing a Vector Error Correction Model (VECM) over the period 2018 to 2016 by employing three groups of indicators (macroeconomics, banking, and monetary). The main finding of the paper is that at the bank level, a tightening of regulatory capital requirements does not induce a higher lending rate in the long run. Also, changes in micro-prudential capital requirements on banks have statistically significant spillovers on the GDP growth rate in the short term; yet, their effects significantly lessen over a longer period.
Keywords: G21; G28; 330; Basel II; regulatory capital requirements; bank capital; lending rate; aggregate growth